Isothermal Drying Kinetic Study of Spent Coffee Grounds Using Thermogravimetric Analysis - Victoria Bejenari; Cătălin Lisa; Corina Cernătescu; Ioan Mămăligă; Gabriela Lisa (International Journal of Chemical Engineering)
Drying coffee grounds involves high energy consumption and represents an important step in using coffee waste materials as green energy. This study analyzes the drying process using thermogravimetric analysis. The kinetics of the drying process of coffee grounds, containing equal proportions of Arabica and Robusta, were evaluated under isothermal conditions at various temperatures: 50, 60, 70, and 80°C, with sample layer thicknesses of 0.6, 1.2, 1.8, and 2.4 mm. The thermogravimetric curves obtained for the coffee grounds samples under conditions of constant temperature allowed the tracing of the drying curves (moisture content—drying time). The influence of the furnace air velocity on the drying and water evaporation process was analyzed. The drying rate has been established to be about 2.6 times slower than the rate of water evaporation under the same conditions; as a result the overall process is controlled by the effective water diffusion in the layer. This aspect is important in industrial practice for sizing tubular dryers. The activation energy was found to be influenced by the thickness of the coffee grounds layer subjected to the drying process and had values between 8.3 kJ/mol and 10.3 kJ/mol.